Sistem Informasi Layanan Pengaduan Sampah di Dinas Lingkungan Hidup Kabupaten Sumba Barat - Novita Boba Laja; Yulius Nahak Tetik; Dian Fransisika Ledi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
This study aims to design and develop a waste complaint information system at the Environmental Agency of West Sumba Regency to improve the effectiveness of public services. The current problem lies in the manual complaint process, which leads to delays in handling reports, poor data documentation, and limited service transparency. This research employs a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation studies. The system development adopts the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system is modeled using Unified Modeling Language (UML), including use case diagrams, activity diagrams, and sequence diagrams to provide a structured representation of the system. This approach is considered effective as it ensures a systematic and well-organized development process. The results indicate that the developed system facilitates the public in submitting complaints online and assists the agency in managing complaint data in an integrated manner. Furthermore, the system enhances response time, transparency, and service efficiency. Therefore, this waste complaint information system can serve as a technological solution to improve the quality of public services.